2018
DOI: 10.1002/jcb.26524
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Silencing of COL1A2, COL6A3, and THBS2 inhibits gastric cancer cell proliferation, migration, and invasion while promoting apoptosis through the PI3k‐Akt signaling pathway

Abstract: This study explores the effect of COL1A2, COL6A3, and THBS2 gene silencing on proliferation, migration, invasion, and apoptosis of gastric cancer cells through the PI3K-Akt signaling pathway. The gastric cancer microarray expression data (GSE19826, GSE79973, and GSE65801) was analyzed. Gastric cancer tissues and corresponding adjacent normal tissues were extracted from patients. Positive expression rate of PI3K, Akt, and p-Akt was measured with immunohistochemistry. Two cell lines, BGC-823 and SGC-7901, were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 39 publications
4
84
0
Order By: Relevance
“…The 43 genes with similar expression patterns are likely to have related functions in the aggressive growth and metastasis of cancers (64). In the PPI network, the genes of AEBP1, MMP14, OLFML2B, PDGFRB, SERPINE1, SPARC, SFRP2, COL1A2, COL6A3, THBS2, COL5A2, COL11A1, FAP, MXRA5 and THY1 were upregulated in solid cancer tissues, and significantly associated with the overall survival of patients with cancer (74)(75)(76)(77)(78)(79)(80)(81)(82). Some genes in the PPI network, including AEBP1, OLFML2B, PDGFRB, SERPINE1, COL1A2, COL6A3, and THBS2 have been reported to be associated with metastasis, invasion and migration in cancer cells (74,76,80,83,84).…”
Section: Discussionmentioning
confidence: 99%
“…The 43 genes with similar expression patterns are likely to have related functions in the aggressive growth and metastasis of cancers (64). In the PPI network, the genes of AEBP1, MMP14, OLFML2B, PDGFRB, SERPINE1, SPARC, SFRP2, COL1A2, COL6A3, THBS2, COL5A2, COL11A1, FAP, MXRA5 and THY1 were upregulated in solid cancer tissues, and significantly associated with the overall survival of patients with cancer (74)(75)(76)(77)(78)(79)(80)(81)(82). Some genes in the PPI network, including AEBP1, OLFML2B, PDGFRB, SERPINE1, COL1A2, COL6A3, and THBS2 have been reported to be associated with metastasis, invasion and migration in cancer cells (74,76,80,83,84).…”
Section: Discussionmentioning
confidence: 99%
“…S7 B , C ). COL6A3, which is positively regulated downstream of PI3K-AKT signaling in ECs (38), was induced at 8 h in WT MLECs but not in Salm4 −/− MLECs (Supplemental Fig. S7 B , C ).…”
Section: Resultsmentioning
confidence: 99%
“…A numbers of previous reports demonstrated that phosphorylation protein form of p-AKT [18][19][20][21][22], p-mTOR [23][24][25][26], p-p38 [27][28][29][30] Fig 3(A, B)). These results indicate that MASTL silencing could inhibit gastric cancer cell invasion and migration in vitro.…”
Section: Discussionmentioning
confidence: 99%